Causal trait theories a new form of person knowledge that explains egocentric pattern projection. [article]. - Critcher, Clayton R.; Dunning, David
Representation of the self and others include not only piecemeal traits but also causal trait theories-explanations for why a person?s standing on 1 trait causes or is caused by standings on other traits (Studies 1a-1c). These casual theories help resolve the puzzle of egocentric pattern projection-the tendency for people to assume that traits correlate in the population in the same way they align in the self. Casual trait theories-created to explain traits co-occurrence in a single person-are exported to guide one?s implicit personality theories about people in general (Study 2) Pattern projection was found to be largely egocentric (i.e., more strong guided by self-than by social perceptions) for 2 reasons. First, causal trait theories are more numerous for the self. When participants were prompted to generate causal trait theories about someone else, they pattern projected more from that person (Study 3). Second, causal trait theories about self are more likely to draw on behavioral information from multiple contexts instead of merely seeking to explain why 2 traits co-occur in a single context. Causal trait theories based on trait-relevant behaviors from different contexts, instead of trait co-occurrence within a single context, produce more pattern projection (Study 4). Implications for self and social cognition are discussed. - - (from the authors)